Pengaruh Penambahan Limbah Peternakan Pada Karakteristik Pembakaran Batubara - Wahyudi, Wahyudi; Santosa, Tito Haji Agung (Universitas Muhammadiyah Yogyakarta, 2008)
Using coal as a fuel is often obstacled in harding of ignition. Waste of farming which is seldom used as fuel possible to mix with coal. Research on solid fuel characteristic of combustion of mixture between coal and waste of farming has been conducted to know the effect of mixture composisition toward rate of combustion. Experiment was conducted in a cylindrical combustion chamber which was heated and flowed with hot air. The content of volatile matter is higher in farming waste than in coal. In combustion of fuel mixture with higher content of farming waste, decreasing of mass of fuel mixture will more rapidly. The maximum combustion rate will higher in fuel mixture consisting more the waste of farming.